Stimulation of 5-HT1A receptors in the dorsal hippocampus and inhibition of limbic seizures induced by kainic acid in rats. - Gariboldi, M. (1996)
1. We studied whether the stimulation of 5-HT1A receptors by 8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DPAT), a specific 5-HT1A receptor agonist, reduced electroencephalographic (EEG) seizures induced by intrahippocampal injection of 0.04 microgram in 0.5 microliter of the glutamate analogue kainic acid in freely-moving rats. 2. Pretreatment with 8-OH-DPAT 15 min earlier at the same site as kainic acid injection, caused a dose-dependent decrease of kainic acid-induced seizure activity. One and 10 micrograms significantly reduced the total time spent in seizures by 72% on average and the total number of seizures by 58% (P < 0.01) and 43% (P < 0.05) respectively. The latency to onset of the first seizure was increased 2.8 times (P < 0.01) only after 1 microgram 8-OH-DPAT; 0.1 microgram was ineffective on all seizure parameters. 3. Systemic administration of 25, 100 and 1000 micrograms kg-1 8-OH-DPAT significantly reduced the total number of seizures and the total time in seizures induced by intrahippocampal kainic acid by 52% and 74% on average. The latency to onset of the first seizure was delayed 1.8 times by 100 and 1000 micrograms kg-1 (P < 0.05). 4. The anticonvulsant action of 8-OH-DPAT given intrahippocampally or systemically was significantly blocked by 5 micrograms, but not 1 microgram WAY 100635, a selective 5-HT1A receptor antagonist, administered in the hippocampus before the agonist. 5. These results indicate that postsynaptic 5-HT1A receptors in the hippocampus mediate the anticonvulsant action of 8-OH-DPAT and that their stimulation has an inhibitory role in the generation of limbic seizures.